Fast transient microjets induced by hemispherical cavitation bubbles - Gonzalez Avila, Silvestre Roberto (2015)
We report on a novel method to generate fast transient microjets and study their characteristics. The simple device consists of two electrodes on a substrate with a hole in between. The side of the substrate with the electrodes is submerged in a liquid. Two separate microjets exit through the tapered hole after an electrical discharge is induced between the electrodes. They are formed during the expansion and collapse of a single cavitation bubble. The cavitation bubble dynamics as well as the jets were studied with high-speed photography at up to 500 000 f.p.s. With increasing jet velocity they become unstable and spray formation is observed. The jet created during expansion (first jet) is in most cases slower than the jet created during bubble collapse, which can reach up to 400 m s−1. The spray exiting the orifice is at least in part due to the presence of cavitation in the microchannel as observed by high-speed recording. The effect of viscosity was tested using silicone oil of 10, 50 and 100 cSt. Interestingly, for all liquids the transition from a stable to an unstable jet occurs at We∼4600. We demonstrate that these microjets can penetrate into soft material; thus they can be potentially used as a needleless drug delivery device.